Driving Entrepreneurial Universities: Commercialization Strategies in Indonesian Universities - Uruqul Nadhif Dzakiy; Mochamad Arief Rahman Ramadhian; Fikri Mohamad Rizaldi (ITB AAS Indonesia Surakarta, 2025)
Universities that initially carried out teaching and research missions are now carrying out a new entrepreneurial mission, which shifted to commercially oriented activities. This research proposes a theoretical framework for commercialization strategy in three leading Indonesian universities; Institut Teknologi Bandung (ITB), Universitas Gadjah Mada (UGM), and Institut Pertanian Bogor (IPB University). Using an abductive approach, the findings show that the Indonesian universities can adopt both technology push and market push in commercializing their research outputs. Each of these strategy adoptions has implications for subsequent commercialization mechanisms, such as by simply optimizing the role of TTOs and incubators or by optimizing holding companies and Science and Technoparks (STPs) by establishing closeness to industry. Keywords : technology commercialization, university, commercialization strategy, technology push, market pull